STRATEGIES FOR COLLECTING ZAKAT, INFAQ, AND SADAQAH (ZIS) FUNDS AT THE BAZNAS YOGYAKARTA CITY - Sutrisno (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2026)
This study examines the fundraising strategies for Zakat, Infaq, and Sadaqah (ZIS) implemented by BAZNAS Yogyakarta City, highlighting a comprehensive and integrative approach that combines both direct and indirect methods. The findings reveal that direct fundraising strategies such as face-to-face engagement and digital platform utilization are effective in generating immediate financial contributions. Meanwhile, indirect strategies play a pivotal role in enhancing public awareness, building trust, and sustaining long-term Muzakki relationships. The success of these approaches is further strengthened by active support from academic institutions, volunteers, and cross-sector collaborations. However, despite these strengths, several structural and operational challenges persist. These include inter-organizational competition, limited human resource capacity and professional certification, inefficiencies in operational processes, and insufficient educational and infrastructural support. Such constraints hinder the optimal performance of fundraising activities, resulting in inconsistencies in achieving targeted ZIS collections. This study underscores the need for strategic improvements through strengthening institutional capacity, enhancing human resource professionalism, optimizing operational systems, and expanding collaborative networks. By addressing these challenges, ZIS fundraising efforts can become more sustainable, effective, and impactful in advancing socio-economic welfare and supporting broader development goals.